Analysis of the Marketing Strategy of Gojek X BTS and Its Impact on the Use of the Gojek Application: A Case Study on the Instagram Account @Gojekindonesia - Abdul Latief; Nur Layla Ali (Publikasi Indonesia, 2026)
The development of technology and information is not a new concept. Technology will continue to evolve from year to year, both in terms of introducing new things and refining existing ones. In Indonesia, there is one technology company that provides transportation services through ojek services for two-wheeled transportation and taxi services using four-wheeled transportation This study aims to determine the marketing strategy of Gojek x BTS impacting the use of the Gojek application in Indonesia through @gojekindonesia Instagram account. The method used in this study is qualitative with a research instrument, namely interviews. The results showed that the use of the Gojek x BTS marketing strategy was successfully carried out which was shown by the increase in the use of the Gojek application where Gojek itself succeeded in increasing its brand awareness through the power of celebrities who are being loved by most teenagers or kpopers in Indonesia. Moreover, the power of social media is very helpful in spreading campaigns which are also proven to have an impact on the use of the Gojek application.